Corn starch 80:20 "waxy":regular, "native" and phosphated, as bio-matrixes for edible films - Gutiérrez Carmona, Tomy José (2015)
Films made from starches are colorless, tasteless, non-toxic, biodegradable, and economical, besides having a low permeability to oxygen. Moreover, the cross-linking modification (phosphatation) could improve its physicochemical properties by reinforcing the hydrogen links inside the granules. The goals of this study were to elaborate and characterize starch corn films 80:20 ?waxy?:regular, from native and modified (cross-linked), to define their potential application. Results showed, that films with modified starch had highest hydrophilic properties which increased its thickness, permeability and solubility, and with mayor stability in acidic and alkaline medium. Finally, physicochemical properties and water vapor barrier data of the films denote the strong interaction phosphated starch-plasticizer.